Immunological biomarkers and injury prevention in athletes - Vermeir, P.; Goethals, A.; Heyerick, M.; Houttekiet, E.; Vermeir, R.; Mariman, A.; Vogelaers, D.; Bossche, L. V. (British Journal of Sports Medicine, 2021)
Background Considering the high incidence and consequences of athletic injuries, it can be beneficial to investigate possible causes and prevention strategies. No previous studies have reviewed the use of biomarkers for prevention and recovery of athletic injuries.